Global warming - Maslin, Mark. (St. Paul, Minn. : Voyageur Press, 2007)
Explores global warming and the evidence that it is really happening and examines the impact it will have on health, agriculture, water resources, coastal regions, forests, and wildlife. Also looks at the efforts that need to be made in order to counteract the effects of global warming.
What is global warming? -- Brief history of global warming -- Who is producing the pollution? -- The evidence for global warming -- The impacts of global warming -- Surprises -- What can we do?
"Updated edition."--Cover.
Includes bibliographical references (p. 72) and index.
Keywords: Global warming -- Juvenile literature; Global warming